Meta-Analysis the Effects of Stretching and Whole Body Vibration Exercise in Reducing Low Back Pain among Heavy Equipment Operator Workers - Melinda Febianca Gaurinindi; Eti Poncorini Pamungkasari; Bhisma Murti (Journal of Epidemiology and Public Health, 2021)
Background: Low back pain is pain due to disc pressure on the nerves that come out through the gap between the vertebrae. Heavy equipment operators have a high risk of developing LBP due to prolonged sitting and vibrations from the machine. This will result in injury and also stiffness in the joints and spine. This study aims to analyze the effect of stretching and whole-body vibration exercise on reducing low back pain in heavy equipment operators/workers.Subjects and Method: This is a meta-analytical study and a systematic review. The articles used were obtained from several electronic databases including Google Scholar, PubMed, Springer Link, Clinical key and ProQuest. The articles used in this study are articles that have been published from 2011-2021. The keywords used in the search were